Technological and Sensory Quality of Gluten-Free Pasta Made from Flint Maize Cultivars - Bongianino, Nicolás Francisco (2023)
The development of quality gluten-free products presents a major technological challenge in terms of structure, texture, and shelf life. However, there is insufficient information available to identify genotypes for obtaining gluten-free maize pasta of good acceptability and technological quality. The objective of this work was to evaluate the technological and sensory quality of gluten-free pasta made from different maize cultivars. The flint open-pollinated variety, flint inbred line, and three dent commercial hybrids were used. Grain and flour’s physical characteristics and chemical composition were determined. Gluten-free pasta was made via extrusion, and its quality traits were studied. A sensory evaluation test was carried out. Flint cultivars showed the lowest values on swelling index (both 1.77) and water absorption (124.30 and 134.58%). Pasta swelling index showed a negative association r = −0.77 to sodium carbonate retention capacity (p = 8.5 × 10−5) and water retention capacity (p = 6.6 × 10−5). Evaluators’ preference results showed a higher frequency of choices at the top level of preference (4) for the flint open-pollinated variety C6006. Thus, evaluators’ choices showed a positive association between sample preference and firmness. Pasta preference and technological quality have a direct relationship with fast tests over grain, such as test weight and float index.